Reverse Segond Fracture Associated with Anteromedial Tibial Rim and Tibial Attachment of Anterior Cruciate Ligament Avulsion Fractures - Yehia H. Bedeir (Case Reports in Orthopedics)
Reverse Segond fracture is an uncommon avulsion fracture of the tibial attachment of the deep portion of the medial collateral ligament of the knee. We report a reverse Segond fracture associated with anterior cruciate ligament tibial avulsion fracture and anteromedial tibial rim fracture. Unlike previous reports, the combination of reverse Segond fracture, anteromedial tibial rim fracture, and anterior cruciate ligament avulsion fracture was not associated with posterior cruciate ligament injury, posterolateral corner injury, or tibial plateau fracture. This new combination of injuries provides better understanding of the mechanisms of ligamentous injuries of the knee and highlights the importance of meticulous assessment of these injuries for accurate diagnosis and subsequent management.